Excavations at a late antique to early Islamic pearling town and monastery on Sīnīya Island, Umm al‑Quwain - Power, Timothy; Degli Esposti, Michele; Hoyland, Robert; Hussein Kannouma, Rania; Borgi, Federico; Iwaszczuk, Urszula; Maini, Elena; Nicolosi, Teresa; Priestman, Seth (Proceedings of the Seminar for Arabian Studies, 2024)
Previous work on Sīnīya Island by the Tourism and Archaeology Department of Umm al‑Quwain, in collaboration with its local and international research partners, revealed the existence of a Christian monastery dating broadly to the seventh and eighth centuries AD. The second season of the Sīnīya Island Archaeological Project continued work at the monastery and opened a new area of excavation in an associated settlement. The settlement constitutes a 10 ha area of dense mounding covered with building materials, pottery, glass, and shells. The ceramic assemblage and buildings typology indicate that the settlement is contemporary with the monastery. Excavations revealed a smaller number of large courtyard buildings surrounded by densely packed small double-roomed buildings, which we might interpret as the houses of merchants and fishermen. Evidence that pearling contributed to the economy was provided by oyster-shell middens, several pearls, and a pearl diver’s weight — the earliest well-dated example yet found in the Emirates. A picture is now emerging of a pearling town and nearby monastery that flourished between late antiquity and early Islam.